Republic of Lithuania : Selected Issues. (IMF Staff Country Reports; Country Report, 2013)
This Selected Issues paper discusses Lithuania's efforts towards a sustainable and inclusive consolidation. Lithuania has implemented fiscal measures amounting to 17 percent of GDP during 2009-2012, about half of which were frontloaded in 2009. The report shows that Lithuania's tax system, in comparison with other European Union member countries, is skewed toward labor and consumption taxes and plays a more limited role in income redistribution, especially in the upper-income brackets. It is highlighted that the country's fiscal adjustment since 2009 has relied mainly on expenditure measures.